Politeness Stylisation in Neo-Victorian Play-by-Post Forum Games - Morozova, Iryna; Nikolaienko, Valeriia (Respectus Philologicus, 2026)
This study examines politeness as a means of character speech stylisation in Neo-Victorian play-by-post role-playing games, which serve as a fusion of creative writing and social simulation. Players adopt Victorian-era discourse strategies, integrating their perceptions of historical politeness with their contemporary linguistic behaviour. Using a corpus of over 36,000 words of character lines from Victorian-themed role-playing forums compared against 19th-century plays, this study focuses on the recurring politeness markers such as hedges, deference and endearment address forms, positive vocabulary, and modal verbs in both samples. While authentic Victorian discourse often features concise or ironic politeness moves, Neo-Victorian players tend to use politeness markers more densely. By applying a cognitive-pragmatic approach, the study reveals that these politeness moves function as construal-enriching operations, serving as a conversation engine in both the authentic Victorian plays and the Neo-Victorian play-by-post creative writing games. The findings highlight the dynamic interplay between historical stylisation and politeness as a conversation-building discourse practice.